Problematika Proses Mediasi Ketenagakerjaan Ditinjau dari Aspek Keadilan (Studi pada Disnakertrans Jawa Timur) - Huri, Daman; Ihtisyam, Hazimah; Izzah, Puteri Nurul; Tsany, Aulia Farahdila; Permatasaridewi, Putri Maharani (Maliyah : Jurnal Hukum Bisnis Islam, 2023)
Mediation is an important element in the alternative scope of labor dispute resolution in Indonesia as well as the mediator. There fore in 2016, PERMA No. 1 of 2016 regarding mediation procedures issued by the government. The settlement of labor disputes in the form of industrial relations between workers and employers of a company which is usually processed at the Manpower and Transmigration Service (Disnakertrans) is also certainly mediated by a neutral party, namely a mediator. The mediator himself is indeed very necessary in this process. Even so, the mediator in carrying out his work will definitely encounter obstacles along the way which will hinder his various duties and authorities, especially in his activities. We have to study these obstacles together so that they don't happen again in the future and can be minimized in such a way. And this of course refers to the laws and regulations related to mediation that the mediator relies on. These obstacles not only hinder the mediator but can also interfere with both parties to the dispute. In this journal, we conduct an in-depth analysis and study of the obstacles encountered in the mediation process, especially labor mediation. Through this research, we were able to find out the implementation of mediation in the East Java Province Manpower and Transmigration Agency. Apart from that, we also identify and analyze some of the common obstacles faced by mediators from the aspect of justice.